2003
DOI: 10.1034/j.1601-0825.2003.02904.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of titanium particles on osteoclast formation generated by treatment of mouse bone marrow cells with PGE2

Abstract: Ti particles inhibited osteoclast differentiation and RANKL expression in mouse bone marrow cells treated with PGE2, without affecting mature osteoclast survival or activity. Thus, Ti particles may alter the osteoclastogenetic action of PGE2, which is one of the regulatory factors of bone remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
1
2
Order By: Relevance
“…The results of the present study are in apparent contradiction with the work of Nakano et al [35]. In their study, Nakano found that Ti particles inhibited RANKL expression in bone marrow cells treated with PGE 2 .…”
Section: Article In Presscontrasting
confidence: 57%
“…The results of the present study are in apparent contradiction with the work of Nakano et al [35]. In their study, Nakano found that Ti particles inhibited RANKL expression in bone marrow cells treated with PGE 2 .…”
Section: Article In Presscontrasting
confidence: 57%
“…Increasing osteoclastogenesis and the inhibition of bone formation is the primary cause of aseptic loosening and osteolysis [ 34 ]. Growing evidence suggests that Ti particle impairs the function of mature osteoblasts as well as inducing osteoclast differentiation [ 35 37 ], which is consistent with the current study. In addition, our results strongly indicate that QUE inhibits Ti-induced osteolysis in vivo as evident by decreased osteoclast numbers and increased bone area.…”
Section: Discussionsupporting
confidence: 92%
“…the beginning of osteoclast generation, researchers found that titanium particles enhanced osteoclast bone resorption ability (16,17). However, this finding contradicts the results of a study by nakano et al, who found that titanium particles had no effect on osteoclast bone resorption activity or on osteoclast survival (18). This contradiction may be due to the differences between the methods used in the two studies; that is, the culture media contained no cytokines while our media contained 1,25(OH) 2 d 3 and PGe 2 .…”
Section: Discussioncontrasting
confidence: 56%